Comparison of the Protective Efficiency of Polymethacrylates with Different Side Chain Length for aa2024 Alloy - Encina-Rojas, M; Paez-Collio, M; Paez-Collio, M; Muñoz-Moena, L; Muñoz-Moena, L; Molina-Ortega, P; Molina-Ortega, P (Elsevier Editora Ltda, 2021)
The protective properties of polymethacrylate coatings with different side chain lengths for 2024 aluminum alloys were studied, focusing on the chain length increase but also on the Ar-plasma pretreatment applied to the metal surface. The coatings were obtained by photopolymerization, obtaining reproducible molecular weight polymers during each process that were determined by high-performance liquid chromatography. AA2024 alloy were immersed into the polymethacrylate solution using methyl, butyl, and hexyl as monomers. Their roughness was then evaluated using atomic force microscopy. Surface hydrophobicity and contact angle hysteresis were analyzed in water and diiodomethane. Protective properties were evaluated by electrochemical impedance spectroscopy after 56 days of immersion in a 0.1 M Na2SO4. The alloy cross-sections were examined by field emission scanning electron microscopy and glow discharge optical emission spectroscopy, allowing the estimation of film thickness. Surface analysis revealed that the defect population densities in the coatings increased the monomer alkyl chain length. The immersion thickness increase was consistent with contact angle measurements taken over time, and independent from the chain length. Contradicting expectations, the results showed the protective efficacy was not related to the chain length, since after exposure, the PBMA film revealed the best anti-corrosive coating performance on the AA2024. This was possibly influenced by its polymeric film conformation, hydrophilicity, ordering and lower density of defects on the metal surface. © 2021 The Author(s)